2022
DOI: 10.1111/iwj.13895
|View full text |Cite
|
Sign up to set email alerts
|

Changes in miroRNA‐103 expression in wound margin tissue are related to wound healing of diabetes foot ulcers

Abstract: To investigate the relationship between small noncoding microRNA-103 (miR-103) and wound healing of diabetic foot ulcers (DFU) and the underlying molecular mechanism, forty type 2 diabetes mellitus with DFU (DFU group), and 20 patients with a chronic skin ulcer of lower limbs and normal glucose tolerance (SUC group) were included. Quantitative real-time PCR method was used to determine miR-103 expression levels in the wound margin tissue of subjects, and to analyse the relationship between the expression of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Samples used to study burn-related miRNAs include adult skin fibroblasts, [18][19][20][21] skin epidermal stem cells, 22 skin, [23][24][25][26][27] wound tissues 28,29 and hypertrophic scar (HS) tissues. [30][31][32][33] Samples used to study wound-healing related miRNAs include healthy skin, [34][35][36] chronic non-healing ulcer tissue, 37,38 epidermal keratinocytes 39 and the HaCaT cell line. [40][41][42][43][44] HS tissues were used to study scarring-related miRNAs.…”
Section: Samples Used To Identify Mirnas Involved In Burn Wound Heali...mentioning
confidence: 99%
See 2 more Smart Citations
“…Samples used to study burn-related miRNAs include adult skin fibroblasts, [18][19][20][21] skin epidermal stem cells, 22 skin, [23][24][25][26][27] wound tissues 28,29 and hypertrophic scar (HS) tissues. [30][31][32][33] Samples used to study wound-healing related miRNAs include healthy skin, [34][35][36] chronic non-healing ulcer tissue, 37,38 epidermal keratinocytes 39 and the HaCaT cell line. [40][41][42][43][44] HS tissues were used to study scarring-related miRNAs.…”
Section: Samples Used To Identify Mirnas Involved In Burn Wound Heali...mentioning
confidence: 99%
“…Other techniques include microarrays (miRCURY LNA, Affymetrix GeneChip, and Agilent) and high throughput sequencing. Although qRT-PCR is the most commonly used technique, only 58 miRNAs were identified in the 27 articles that utilised the technique, [18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][45][46][47][48][49][50] while the expression level of 82 miRNAs were measured by sequencing in two research studies. 22,38 In comparison, alterations in the expression of 203 miRNAs were detected using three different microarrays in seven research studies.…”
Section: Techniques Used To Measure Mirna Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Downregulation of miR-103 mitigated hyperglycemia-induced HSF injury by promoting RCAN1 expression, so it can promote wound repair by inhibiting the expression of miR-103. 28 Another study found that miR-27-3p was overexpressed in the wounds of diabetic mice and patients. The decreased level of its downstream target neurooncological ventral antigen 1 in fibroblasts was shown to cause less proliferation and extracellular matrix production but more apoptosis.…”
Section: Abnormal Mirs In Local Woundsmentioning
confidence: 99%
“…A study found that patients with DFUs had a much 2.5-fold higher risk of death than patients without lower extremity wounds, with an estimated 5-year mortality rate of 42% for patients with DFUs ( 4 ). Although various drugs are availabled for DFUs, the ulcers usually remain refractory and impact the quality of life of patients ( 5 ). Therefore, it is essential to investigate new strategies to accelerate healing of these cutaneous ulcers.…”
Section: Introductionmentioning
confidence: 99%